2012
DOI: 10.3389/fonc.2012.00019
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Cancer in Benign Brain Tumor Subtypes Versus Gliomas

Abstract: Purpose: Family history is associated with gliomas, but this association has not been established for benign brain tumors. Using information from newly diagnosed primary brain tumor patients, we describe patterns of family cancer histories in patients with benign brain tumors and compare those to patients with gliomas. Methods: Newly diagnosed primary brain tumor patients were identified as part of the Ohio Brain Tumor Study. Each patient was asked to participate in a telephone interview about personal medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…1). Here, using the Ohio Brain Tumor Study (OBTS), 7 we identified 2 cohorts of glioma patients: long-term survivors (LTS, average 33 mo overall survival [OS]) and short-term survivors (STS, average 7 mo OS). We employed genomic analyses (exome, whole genome sequencing), transcriptomic sequencing, and methylation profiling to assemble an integrated genomic landscape for gaining insight into the underpinning mechanism(s) associated with the survival differences.…”
mentioning
confidence: 99%
“…1). Here, using the Ohio Brain Tumor Study (OBTS), 7 we identified 2 cohorts of glioma patients: long-term survivors (LTS, average 33 mo overall survival [OS]) and short-term survivors (STS, average 7 mo OS). We employed genomic analyses (exome, whole genome sequencing), transcriptomic sequencing, and methylation profiling to assemble an integrated genomic landscape for gaining insight into the underpinning mechanism(s) associated with the survival differences.…”
mentioning
confidence: 99%
“…A média de idade foi de 47 anos, mostrando igualdade com outro estudo realizado em Porto Alegre. 7 Em estudo de Ostrom et al, 8 a prevalência do sexo feminino também foi constatada, e a observação da prevalência feminina pode ser associada aos hormônios envolvidos no desenvolvimento e no crescimento de tumores cerebrais em mulheres, principalmente os meningiomas, pois estudos mostram que existe a presença de receptores de progesterona nas células desse tipo tumoral. 9 Em estudo realizado nos Estados Unidos, dois terços dos tumores relatados eram gliomas ou meningiomas (66,2%), 10 dado que coincide com o encontrado no presente estudo, em que gliomas e meningiomas somam 66% dos casos.…”
Section: Discussionunclassified
“…In this particular study, we utilized retrospective data with available preoperative MRI (T1, T2, T1-Gd, T2-FLAIR) from patients diagnosed with gliomas from 3 collections, all being part of the ReSPOND consortium 17 (collection 1 [ n = 248]: Hospital of the University of Pennsylvania [HUP]; collection 2 [ n = 192]: The Cancer Imaging Archive [TCIA]; collection 3 [ n = 33]: Ohio Brain Tumor Study 18 , 19 ; Table 1 ). Data from collection 1 also had advanced MRI, including DSC-MRI and diffusion-weighted imaging (DWI), available.…”
Section: Methodsmentioning
confidence: 99%